Primary processing of experimental data of modern testing machine for identification of rheological models - Adamov, Anatoliy Arsangaleevich (Computational Continuum Mechanics, 2013)
The procedures of compression, smoothing, filtration and correction of experimental data in the form of time series recorded by modern test machines are considered. The piecewise-continuous approximations are obtained by using Chebyshev polynomials and best spline approximations going through the first prescribed point on the sections between neighboring points of discontinuity in the first derivative. The iteration procedures for constructing polynomials and splines based on different optimality criteria and data selection have been realized.